Gambaran Karakteristik dan Pengetahuan Penderita Tuberkulosis dalam Upaya Pencegahan Penularan di Wilayah Kerja Puskesmas Samata Kab Gowa - Mirawati Mirawati; Sartika Sartika; Kasmawati Kasmawati; Asrul Muarif; Rintoh Rintoh (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2026)
Tuberculosis (TB) is an infectious disease caused by the bacteria mycobacterium tuberculosis. The germ usually enters the human body through the air inhaled into the lungs. TB is one of the infectious diseases that is still a health problem in the world today. Research Objective: To determine the characteristics and knowledge of tuberculosis patients in efforts to prevent transmission of tuberculosis in the work area of the Samata Health Center, Gowa Regency. Research Method: This study uses a descriptive design method. The population in this study were all Tuberculosis patients who were treated in May in the working area of the Samata Health Center, Gowa Regency. The sampling technique in this study was Accidental Sampling with a sample size of 30 people. Research Results: Based on the results of the study, the knowledge of respondents with tuberculosis regarding efforts to prevent the spread of tuberculosis in the work area of the Samata Health Center, Gowa Regency, was highest in the sufficient category, with 27 people (90.0%) and the lowest was in the good category, with 3 people (10.0%). Conclusion: Based on the results of the study, knowledge is in the Sufficient category, namely 27 people (90.0%). It is expected that respondents can be more active in digging up information that can further increase their knowledge.